2016
DOI: 10.1080/09581596.2016.1208362
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perceptions of universal health coverage and its implications for the Kenyan health sector

Abstract: Koon, A.D.;Smith, L.; Ndetei, D.; Mutiso, V.; Mendenhall, E. (2016) [Accepted Manuscript] Nurses perceptions of universal health coverage and its implications for the Kenyan health sector. Critical public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…showed that nurses with UHC were completely unfamiliar and offered numerous interpretations that could undermine the move toward UHC. [ 26 ] We design the strategic thinking module to achieve the goals of community coverage by providing nurses with an overview of foresight skills and system dynamics. The UHC can meet its primary goal of better health and is not a new concept, but it requires doctors and nurses to be adequately trained and knowledgeable about the overall health system and ensuring proper access to services.…”
Section: Discussionmentioning
confidence: 99%
“…showed that nurses with UHC were completely unfamiliar and offered numerous interpretations that could undermine the move toward UHC. [ 26 ] We design the strategic thinking module to achieve the goals of community coverage by providing nurses with an overview of foresight skills and system dynamics. The UHC can meet its primary goal of better health and is not a new concept, but it requires doctors and nurses to be adequately trained and knowledgeable about the overall health system and ensuring proper access to services.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing inequities in access to and utilization of health services is a major challenge in the Kenyan health system [41], and this study reveals the ways in which health care workers' strikes may further entrench these inequities, both in terms of acute impacts on access to services during strikes as well as overall trust in these services that affect care seeking in the future. The 2017 strikes occurred as the government was rolling out a universal maternal child health policy, Linda Mama, and while health care workers largely support universal health initiatives in Kenya, they feel unsupported and ill-equipped to implement these policies on the ground [42]. Additionally, in this study CHVs articulated their own precarious working conditions in the health system as unpaid but critically important actors when speaking about health care workers' strikes.…”
Section: Discussionmentioning
confidence: 89%
“…Doctors interpreted this to be responsible for two subsequent developments. First, in 2013, the newly elected National Rainbow Coalition pushed to increase healthcare utilization through free maternity care and removal of user fees, overwhelming an exasperated health workforce (Koon et al 2017). Second, following devolution, public practitioners would become employees of county health departments, with unclear, politicized mandates (Kimathi 2017).…”
Section: U N E D I T Ementioning
confidence: 99%